Evaluation of the Implementation of Child-Friendly Services at Kelapa Gading Public Health Center - Rusmini Redjeb; Henni Sari Dewi; Sri Rahayu (Universitas Ibn Khaldun Bogor, 2026)
Study This aim for evaluate implementation Child-Friendly Services (PRA) at Kelapa Gading Health Center with focus on policy, commitment, implementation, role cross sector, participation society, as well as perspective power health, visitors, and staff security. Research use approach qualitative descriptive with technique data collection through interview in-depth, observation, and study documentation. Data analysis was carried out using analysis models Miles and Huberman's interactive research results show that Kelapa Gading Health Center has own clear internal policies and guidelines related to PRAP, as well as commitment leadership and workforce health in apply it in a way consistent. Support cross sectors and participation active community, including parents and cadres integrated health post, plays a role important in create environment safe, comfortable and enjoyable service for children. The implementation of PRAP takes into account appropriate communication age, comfort physical, procedures safe, and involvement officer security for guard order and safety children. Research This confirm that service friendly children at the Kelapa Gading Health Center are implemented in a way holistic, systematic, and sustainable, with consider aspect clinical, psychological, social, and participation active children and families. Findings This can become base service strategy improvement and development health older children effective in facilities service primary health.